Barium titanate particle dispersion liquid and method for producing the same

By utilizing a dispersion of BTO particles with a wide particle size distribution, the issue of low film density in BTO films is addressed, resulting in enhanced dielectric and refractive properties and enabling the production of thinner, more efficient electronic components.

JP2025059248APending Publication Date: 2025-04-10JGC CATALYSTS & CHEMICALS LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023169210
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing methods for forming barium titanate (BTO) films suffer from low density due to gaps between particles, which affects the dielectric constant and refractive index, and amorphous BTO sintering aids struggle to fill these gaps effectively.

Method used

A dispersion of BTO particles with a wide particle size distribution, characterized by a median particle size of 2 to 5 nm and a difference of 30 nm or more between the maximum and median particle sizes, is used to fill gaps between larger particles, increasing film density.

Benefits of technology

The wide particle size distribution allows smaller particles to fill gaps between larger ones, resulting in a denser film with improved dielectric and refractive properties, and enabling thinner, more efficient electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059248000001
    Figure 2025059248000001
Patent Text Reader

Abstract

To provide a BTO particle dispersion liquid having a wide particle size distribution.SOLUTION: The present invention provides a dispersion liquid of barium titanate particles having a perovskite structure, in which: a median particle size (D50) measured by a dynamic light scattering method is 2 to 5 nm; a difference between a maximum particle size (D100) and the median particle size (D50) measured by the dynamic light scattering method is 30 nm or more; and a proportion of a particle size of 5.4 nm or less measured by the dynamic light scattering method is 70% or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a dispersion of barium titanate particles and a method for producing the same.

[0002] Barium titanate (BTO) with a perovskite structure exhibits high dielectric constant and refractive index, and is therefore used in optical modulators and switches, multilayer ceramic capacitors (MLCCs), optical filters, and the like of electro-optical devices. In these applications, BTO particles are used in the form of thin films, as they are becoming lighter, thinner, shorter, and smaller. Such thin films are formed by applying a dispersion of BTO particles onto a substrate (see, for example, Patent Document 1). When a dispersion of BTO particles is used as in Patent Document 1, gaps are formed between the BTO particles (hereinafter, the gaps between the BTO particles are referred to as gaps), and the density of the film is low. In such a film, it is difficult to obtain the characteristics of the BTO particles, such as the dielectric constant and refractive index. In order to increase the density of the film, a method is known in which amorphous BTO is used as a sintering aid (see, for example, Patent Document 2). Patent Document 2 shows that the capacitance of a multilayer ceramic capacitor (MLCC) can be increased by applying such a film to the dielectric layer of the MLCC. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-240904 A [Patent Document 2] JP 2005-306691 A Summary of the Invention [Problem to be solved by the invention]

[0004] In Patent Document 2, an attempt is made to obtain a dense film by using amorphous BTO, but the difference in particle size between the BTO particles in the dispersion and the amorphous BTO is small. In other words, the particle size distribution of the dispersion is narrow, so there is a problem that the amorphous BTO does not easily fill gaps. [Means for solving the problem]

[0005] The dispersion of BTO particles according to the present invention has a median particle size (D50) of 2 to 5 nm as measured by dynamic light scattering, a difference between the maximum particle size (D100) and the median particle size (D50) as measured by dynamic light scattering of 30 nm or more, and a proportion of particles having a particle size of 5.4 nm or less as measured by dynamic light scattering of 70% or more. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0006] In the dispersion of BTO particles of the present invention, the difference between the maximum particle size (D100) and the median particle size (D50) is 30 nm or more. In other words, the particle size distribution of the dispersion is wide. By forming a film of BTO particles using this dispersion, the gaps between the relatively large BTO particles (hereinafter referred to as large particles) present in the dispersion are filled by smaller BTO particles (hereinafter referred to as small particles). This increases the density of the film.

[0007] Furthermore, the proportion of particles of 5.4 nm or less in the dispersion is set to 70% or more. This increases the proportion of small particles in the dispersion, and increases the amount of gaps that can be filled. Also, the smaller the small particles and the greater the proportion of small particles, the easier it is for them to fill the gaps. Therefore, the proportion of particles of 3.2 nm or less in the dispersion is preferably 30% or more. On the other hand, the proportion of particles of 5.4 nm or less in the dispersion is preferably less than 99%. Since there are at least 1% or more particles larger than 5.4 nm, the number of small particles that cannot fit into the gaps is reduced. Here, the proportion of particles is the proportion of the volume of the particles to the total volume of the particles in the dispersion (100%).

[0008] Furthermore, the smaller D50, the thinner the film that can be formed. The thinner the film, the more compact the electronic components to which the film is applied can be. Furthermore, when the film is applied to an MLCC, the capacitance of the MLCC can be increased. Therefore, D50 is 5 nm or less. On the other hand, if D50 is too small, there is a high possibility that insufficiently crystallized particles (amorphous, etc.) will be included, resulting in a low dielectric constant. Therefore, D50 is 2 nm or more.

[0009] When a film containing amorphous barium titanate is fired, the amorphous barium titanate shrinks, resulting in the formation of voids. In other words, the smaller the amount of amorphous in the solid content of the dispersion, the fewer the voids in the film produced using this dispersion. Even if no voids are formed, the film is subjected to stress upon firing, causing cracks or bending of the film. For these reasons, when the solid content of the dispersion is measured by XRD, the diffraction intensity I at a diffraction angle of 26° is A and the intensity of the main peak of the perovskite structure I p Ratio to (I A / I p ) is preferably 0.2 or less, and more preferably 0.1 or less.

[0010] In addition, the particle size distribution of the dispersion liquid is preferably a broad spectrum. This dispersion liquid contains small particles of various sizes. Therefore, by using this dispersion liquid, gaps of various sizes can be filled with small particles. In other words, when this dispersion liquid is used, it is easier to fill the gaps in the film with small particles than when a dispersion liquid whose particle size distribution is a spectrum of emission lines is used. When the particle size distribution of the dispersion liquid is a broad spectrum, the particle size distribution of the dispersion liquid is preferably a multi-modal spectrum, and particularly preferably a bimodal spectrum.

[0011] Also, the smaller D100 is, the easier it is to make the film thinner. Therefore, D100 is preferably 100 nm or less, more preferably 90 nm or less, and even more preferably 70 nm or less. Also, the ratio (D100 / D50) is preferably 13 or more. The higher this ratio is, the easier it is to fill small particles in the gaps.

[0012] The BTO particles may contain a doping element. Examples of the doping element include lanthanide, actinide, and elements of Groups 2 to 14. The electrical properties of the BTO particles, such as the dielectric constant, can be adjusted by using these doping elements. From the viewpoint of increasing the dielectric constant of the BTO particles, the amount of the doping element in the BTO particles is preferably 10% by weight or less.

[0013] Moreover, the higher the proportion of barium titanate in the solid content, the higher the dielectric constant of the BTO particles. From the viewpoint of increasing the dielectric constant of the BTO particles, the proportion of barium titanate is preferably 50% by weight or more, more preferably 70% by weight or more, and even more preferably 90% by weight or more.

[0014] Examples of the shape of the BTO particles include spheres, ellipsoids (rugby balls), cocoons, confetti, chains, cubes, etc. Spherical BTO particles tend to be densely packed in the film.

[0015] The dispersion contains a solvent to disperse the BTO particles. Water or an organic solvent can be used as the solvent. When a highly polar organic solvent is used, the BTO particles can be dispersed in the solvent without using a surface treatment agent. An example of a highly polar organic solvent is alcohol.

[0016] On the other hand, when an organic solvent with low polarity is used, the BTO particles can be easily dispersed in the organic solvent by treating the surface of the BTO particles with a surface treatment agent. Examples of organic solvents with low polarity include solvents having a hydrophobic portion such as an alkyl group having 5 or more carbon atoms or a cyclic structure (e.g., a five-membered ring or a benzene ring).

[0017] The higher the solid content concentration of the dispersion, the lower the transportation cost. Therefore, the solid content concentration is preferably 5% by weight or more. On the other hand, the lower the solid content concentration, the less likely the BTO particles are to aggregate. Therefore, the solid content concentration is preferably 40% by weight or less.

[0018] Next, a method for producing the dispersion will be described. The dispersion is prepared by mixing a first dispersion and a second dispersion having different average particle sizes. The particle size distribution of the dispersion is broader than that of the first dispersion and the second dispersion. The first dispersion and the second dispersion preferably have the characteristics of the dispersion described above in addition to the particle size distribution.

[0019] When a film is formed, the particles in the dispersion are filled into the film with their original size, so the size of the particles dispersed in the dispersion (dispersed particle size) affects the film's thickness and density. Since the size of the dispersed particle size is an important factor in the film's thinness and density, the form of the particles in the dispersion can be either primary particles (crystallites) or secondary particles (particles formed by agglomeration of crystallites).

[0020] When the solvent of the prepared dispersion is replaced with an organic solvent with low polarity, it is preferable to treat the surface of the BTO particles with a surface treatment agent (surface treatment). It is easier to uniformly treat the surface of the BTO particles in a dispersion with a narrow particle size distribution than in a dispersion with a broad particle size distribution. Therefore, it is preferable to treat the surface of the BTO particles in the first dispersion and the second dispersion, respectively, and then mix the first dispersion and the second dispersion.

[0021] Examples of methods for preparing the first dispersion liquid and the second dispersion liquid include a solid phase method, a coprecipitation method, an oxalic acid method, and an alkoxide method. For example, the following method for producing a dispersion liquid can be used. First, a first dispersion liquid containing BTO particles with a primary particle diameter (crystallite diameter) of 5 to 15 nm is prepared. Next, a second dispersion liquid containing BTO particles with a primary particle diameter of 17 to 25 nm is prepared. Here, in these dispersion liquids, the particles are dispersed in a solvent in the form of primary particles (primary particle dispersion liquid). Next, a dispersion liquid is prepared by mixing the first dispersion liquid and the second dispersion liquid.

[0022] Specifically, the primary particle dispersion liquid can be prepared by the following method. A mixed liquid of barium hydroxide and alkyl cellosolve is prepared (first step). This mixed liquid is dehydrated at 40°C or higher (second step). Titanium alkoxide is added to the mixed liquid (third step). A solvent containing water is added to the mixed liquid (fourth step). The mixed liquid is aged (fifth step). By aging, barium titanate crystallizes in the mixed liquid, and BTO particles are obtained. If the aging temperature is 20°C to 40°C, the average particle size will be 17 to 25 nm. If the aging temperature is 50°C to 100°C, the average particle size will be 5 to 15 nm.

[0023] [Example 1] The method for producing the BTO particles and their physical properties will be specifically described below.

[0024] [Preparation of first dispersion] <First step> 100 g of barium hydroxide octahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 630 g of 2-methoxyethanol (methyl cellosolve) were placed in a 1 L beaker and mixed. The mixture was irradiated with ultrasonic waves at 40°C for 30 minutes to dissolve part of the barium hydroxide, obtaining a mixed solution.

[0025] <Second process> The mixture was placed in a 2L eggplant flask and distilled under reduced pressure using an evaporator. The distillation was carried out for 1 hour at 70°C and 15 hPa. The undissolved compounds were then precipitated by centrifugation. The supernatant (mixed liquid) was decanted to separate the precipitate (undissolved compounds). The precipitate was white. The centrifugation conditions were 3000 rpm and 15 minutes. The barium concentration of the supernatant (mixed liquid immediately before adding titanium alkoxide) measured by ICP-OES was 15.5 wt% and the water content was 0.49 wt%.

[0026] <Third step> Titanium alkoxide was added to 100 g of the supernatant obtained in the second step so that the atomic ratio (Ba / Ti) was 1.00. That is, in a glove box under a nitrogen gas atmosphere, 32.1 g of tetraisopropoxy titanium (Orgatix (registered trademark) TA-8 manufactured by Matsumoto Fine Chemical Co., Ltd.; Ti concentration 16.85 wt%) was added to 100 g of the supernatant to prepare a mixture.

[0027] <Fourth process> A mixed solvent of 48.9 g of methanol and 16.3 g of water was added to the mixture over 1 minute while stirring the mixture, and the mixture was then stirred at room temperature for 1 hour to obtain a hydrate gel.

[0028] <Fifth process> A BTO particle dispersion with a crystallite size of 8 nm was obtained by aging the hydrate gel at 80° C. for 48 hours. A first dispersion (solid concentration 30%) was obtained by replacing the solvent in the BTO particle dispersion with butyl carbitol.

[0029] [Preparation of second dispersion] While stirring the mixture obtained in the third step of preparing the first dispersion, a mixed solvent of 97.5 g of methanol and 32.5 g of water was added to the mixture over 1 minute, and the mixture was stirred at room temperature for 1 hour to obtain a hydrate gel. The hydrate gel was heated to 25°C and aged for 96 hours to obtain a BTO particle dispersion with a crystallite size of 20 nm. The obtained BTO particle dispersion was subjected to solvent substitution with butyl carbitol to obtain a second dispersion (solid concentration 30%).

[0030] [Preparation of Dispersion] A dispersion was obtained by mixing the first dispersion and the second dispersion in a solid content weight ratio of 1: 1. The solid content weight was measured in the same manner as in the measurement of solid content concentration (3) described later.

[0031] The preparation conditions of the dispersion liquid are shown in Table 1 together with other examples and comparative examples. The properties of the obtained dispersion liquid were measured by the following methods. The measurement results of the other examples and comparative examples are shown in Table 1 together.

[0032] (1) Particle size After filling the measurement cell with 1 g of the dispersion liquid, a dropper was used to suck up the liquid in the cell to make the cell uniform, and then the liquid was returned to the cell. This operation was repeated twice to prepare the sample for measurement. The particle size distribution (volume basis) was measured by dynamic light scattering using a particle size distribution device (Nanorakku UPA-UT151 manufactured by Nikkiso Co., Ltd.). From the particle size distribution, the median D50, maximum particle diameter D100, percentage of particles 5.4 nm or less, and percentage of particles 3.2 nm or less were obtained.

[0033] (2) Crystal structure The dispersion was dried at 150°C to obtain a powder, which was then pulverized to prepare a sample for measurement. The crystal structure was measured using an X-ray diffraction measuring device, Rigaku's MiniFlex (registered trademark) 600. The crystal structure can be identified using analysis software PDXL2. The half-width β of the peak near 2θ=31.5° of the perovskite structure (when the crystal structure is cubic, the half-width of the Miller index (110) is measured, and when the crystal structure is tetragonal, the half-width of the Miller index (101) is measured). The crystallite diameter was calculated from the half-width β (rad) using Scherrer's formula "D=Kλ / βcosθ". Here, D is the crystallite diameter (Å), K is the Scherrer constant, λ is the X-ray wavelength (1.7889 Å), and θ is the reflection angle. Peak search (hybrid search match) was performed using analysis software PDXL2 (version 2.0.3.0). The crystal structures of the first and second dispersions were also measured in the same manner. The crystallite diameter of the first dispersion was 8 nm, and that of the second dispersion was 20 nm.

[0034] (3) Solid content concentration 1 g of the dispersion was placed in a crucible and heated to 350°C using a hot stirrer to dryness. It was then fired at 1000°C for 1 hour. After cooling, the weight was measured and the solid content weight was calculated. The solid content concentration was calculated by dividing the solid content weight by the weight of the dispersion.

[0035] A substrate (silicon wafer) with a transparent coating was prepared by the following method. The porosity of the substrate (silicon wafer) with a transparent coating was evaluated using a spectroscopic ellipsometer (SE-2000 manufactured by Nippon Semilab Co., Ltd.). The presence or absence of cracks was also visually confirmed. The measurement results of other examples and comparative examples are shown in Table 1.

[0036] [Preparation of substrate (silicon wafer) with transparent coating] The dispersion was applied to a silicon wafer (6-inch dummy wafer (P type) manufactured by Matsuzaki Seisakusho Co., Ltd., thickness: 625 μm) by spin coating. This dispersion was dried at 150 ° C for 5 minutes, and then baked at 550 ° C for 5 minutes to prepare a substrate (silicon wafer) with a transparent coating. Using a spectroscopic ellipsometer (SE-2000 manufactured by Nippon Semilab Co., Ltd.), the Ψ (amplitude ratio angle between p-polarized light and s-polarized light) and Δ (phase difference between p-polarized light and s-polarized light) of the substrate with the transparent coating were measured by spectroscopic ellipsometry. The measurements were performed at a temperature of 25 ° C, two angles of incidence (70 °, 75 °), and measurement wavelengths of 250 to 1650 nm. The porosity in the transparent coating was calculated by fitting analysis using Bruggeman's effective medium approximation (EMA) on analysis software (SEA manufactured by SEMILAB Co., Ltd.) for Ψ and Δ obtained by spectroscopic ellipsometry. The fitting analysis was performed as follows. An optical model consisting of (BaTiO3 (Tauc-Lorentz dispersion equation + Gauss dispersion equation) + Void (nk file included in the analysis software)) / c-Si (nk file included in the analysis software) was applied to the EMA, and Ψ and Δ were simulated using the film thickness, the volume fraction of BaTiO3 and void, each parameter of the BaTiO3 dispersion equation, and the dielectric constant ε1 at infinite wavelength as analysis variables, and fitting was performed to the measured data. The void volume fraction when the fitting error was smallest was taken as the porosity. The R2 value at this time is also shown in Table 1.

[0037] [Example 2] The dispersion obtained in Example 1 was diluted with butyl carbitol to a solid content concentration of 10% by weight, and this was used as a dispersion.

[0038] [Example 3] In preparing the dispersion, the solid content weight ratio was set to 25:75. Other than that, the same procedure was followed as in Example 1.

[0039] [Example 4] In preparing the dispersion, the solid content weight ratio was set to 33:67. Other than that, the procedure was the same as in Example 1.

[0040] [Example 5] In preparing the dispersion, the solid content weight ratio was set to 67:33. Other than that, the procedure was the same as in Example 1.

[0041] [Example 6] In preparing the dispersion, the solid content weight ratio was set to 75:25. Other than that, the same procedure as in Example 1 was carried out.

[0042] [Comparative Example 1] A "barium titanate powder (dispersion liquid)" was prepared in the same manner as in Example 1 of Patent Document 2, and this was used as the dispersion liquid.

[0043] [Comparative Example 2] The dispersion obtained in Comparative Example 1 was concentrated by an evaporator to a solid content concentration of 12% by weight, and this was used as a dispersion. This dispersion was applied to a silicon wafer by spin coating in the same manner as in Example 1. When this was dried at 150°C for 5 minutes to form a film, the film peeled off from the silicon wafer and could not be evaluated.

[0044] [Comparative Example 3] In preparing the dispersion, the solid content weight ratio was set to 0:100. Other than that, the procedure was the same as in Example 2.

[0045] [Comparative Example 4] In preparing the dispersion, the solid content weight ratio was set to 100:0. The rest was the same as in Example 2.

[0046] [Table 1]

Claims

1. A dispersion of barium titanate particles having a perovskite structure, The median particle size D50 measured by dynamic light scattering is 2 to 5 nm; the difference between the maximum particle size D100 and the median particle size D50 measured by a dynamic light scattering method is 30 nm or more; A dispersion of barium titanate particles, in which the proportion of particles having a size of 5.4 nm or less is 70% or more when the dispersion is measured by a dynamic light scattering method.

2. 2. The dispersion according to claim 1, wherein the proportion of particles having a size of 3.2 nm or less is 30% or more when the dispersion is measured by dynamic light scattering.

3. When the solid content of the dispersion was measured by XRD, the diffraction intensity I at a diffraction angle of 26° was A and the intensity I of the main peak of the perovskite structure p Ratio to (I A / I p 2. The dispersion according to claim 1, wherein the σ is 0.2 or less.

4. A method for producing a film-coated substrate, comprising forming a film on a substrate by using the dispersion according to claim 1.

Citation Information

Patent Citations

  • Barium titanate powder and method of manufacturing the same

    JP2005306691A

  • Method for producing crystalline titanic acid salt, and crystalline titanic acid salt

    JP2012240904A